Pandemic COVID-19: Current status and challenges of antiviral therapies - Winglam Chan; Betsy He; Xiong Wang; Ming-Liang He (Genes and Diseases, 2020)
The pandemic COVID-19, caused by a new coronavirus SARS-CoV-2 infection, has infected over 12 million individuals and caused more than 55,200 death worldwide. Currently, there is no specific drug to treating this disease. Here we summarized the mechanisms of antiviral therapies and the clinic findings from different countries. Antiviral chemotherapies have been conducted by in multiple cohorts in different counties. Although FDA has fast approved remdesivir for treating COVID-19, it only speeds up recovery from COVID-19 with mildly reduced mortality. The chloroquine was suggested a potential drug against SARS-CoV-2 infection due to its in vitro antiviral effects, it is imperative high-quality data from worldwide clinical trials are necessitated for an approved therapy. In terms of hydroxychloroquine (HCQ) therapy, although WHO has stopped all the clinic trials due to its strong side-effects in COVID patients, large scale clinical trials with a long-term outcome follow-up may warrant HCQ and azithromycin combination in combating the virus. Convalescent plasma (CP) therapy suggested its safety use in SARS-CoV-2 infection; but both CP immunotherapy and NK cellular therapy must be manufactured and utilized according to scrupulous ethical and controlled conditions to guarantee a possible role of these products of human origin. Further research should be conducted to define the exact mechanism of SARS-CoV-2 pathogenesis, suitable animal models or ex vivo human lung tissues aid in studying replication, transmission and spread of the novel viruses, thereby facilitating highly effective therapies.